Processo do adoecer e itinerários terapêuticosde pessoas com uso problemáticode álcool em busca de cuidados à saúde - Santos, Sheilla Carla Neves dos (2018)
Alcohol is a public health problem, one of the most significant risk causes for morbidity, mortality and disability worldwide. And its consequences are numerous for the citizen, family and society directly and indirectly. To this end, this study aimed to describe the life history of people who use problematic alcohol, understand their health disease process regarding the problematic use of alcohol and analyze the therapeutic itineraries of people in problematic alcohol use in search of health care in the municipality of Irecê - BA. Methodology: Qualitative research conducted in Irecê / BA, CAPS type II, family health unit (USF) Antônio Diniz and Therapeutic Community G. Livre Maanaim, with 13 participants in problematic alcohol use. We used as data production technique, narrative interview of Schütze. Results: in the participants' history, alcohol consumption starts in adolescence, family, parties or / and among friends to belong to the group. Negative consequences of problematic use include job loss, low self-esteem, domestic violence, physical and psychological distress. The therapeutic itinerary includes informal family care, religious faith and professional care, not restricted to mental health institutions. Thus, they seek a variety of alternatives such as the “strength” of family, friends, and neighbors, even of strangers for the sake of defending the other's life, regardless of the formal health and service institutions considered non-formal as evangelical, Catholic churches. , spiritualism and healerism. Considerations Endings: The life story of these people, for the most part, permeates experiences of family disorganization, violence and other social and cultural determinants, leading them to loss of self-esteem, humiliation, social rejection, lack of love, hopelessness, material loss, among others. Also, they have been looking for opportunity in your life - Resilience. Finally, they circulate in a poorly articulated care network, which reflects directly on their therapeutic itinerary, fixing them in certain services. In view of the results, we highlight the need to improve attention to people with problematic alcohol use through a health care network articulated not only with services but also with health professionals prepared to work with resolve, comprehensiveness, welcoming, bonding, accountability and commitment for the defense of the lives of all users, family members and society, since HEALTH is everyone's RIGHT and the DUTY of the State.